Kejadian Obesitas dan Hubungannya dengan Defisiensi Fe pada Anak Usia Sekolah: Tinjauan Sistematis: Occurrence of Obesity and Its Relation to Fe Deficiency in School-Age Children: A Systematic Review - Wilis Cahyaning Ayu; Devina Nathania; Rahmatya Ikhwanurrosida; Siti Rahayu Nadhiroh (Amerta Nutrition, 2023)
Background: The problem of nutritional health in society is a crucial topic widely reported in developed and developing countries. The incidence of Fe deficiency in children is associated with obesity, including overweight, but the relationship between the two is still being identified further. Objectives: To identify the relationship between obesity in school-aged children (7-19 years) and Fe deficiency and the specific parameters used through a systematic review. Methods: This research was conducted with a systematic review using PubMed, Scopus, and ScienceDirect databases. The literature search strategy was carried out through evidence software by entering predefined inclusion and exclusion criteria. Five kinds of literature were selected from 2015 to 2021. Discussions: Fe deficiency is defined as the presence of two or more abnormal values ​​of the following parameters: (i) serum ferritin (SF) <15µg/L (ii) serum iron (SI) <10.7 µmol/l; (iii) Total iron Binding Capacity (TIBC) >62.7 µmol/l; dan (iv) %transferrin saturation (%Tsat) <15%. Fe deficiency in obese conditions occurs through an increase in proinflammatory mechanisms and the role of leptin which can reduce the availability and absorption of Fe in the body. Parameters soluble transferrin receptor (sTfR) is the best parameter to identify Fe deficiency in obese individuals. At the same time, serum ferritin (SF) has limitations as an indicator of iron status in obese children. Conclusions: These findings indicate that the incidence of obesity in children may lead to an increased risk of iron deficiency. The problem of iron deficiency and obesity is a public health problem that has detrimental short and long-term health effects, especially for school-age children in a phase of cognitive growth and development. The sTfR parameter is not significantly affected by inflammation due to adiposity, so it can differentiate iron deficiency from inflammatory hypoferremia.